23: THE HEN‐BROOD RELEASE AS A RESTORATION TECHNIQUE - Gene Rush (Wildlife Society Bulletin)
ABSTRACT As a result of turkey management and restocking in Arkansas in the past 10 years, several conclusions have been reached. The trapping of hens with broods for releases to restock has many advantages. The hen with young is much easier to trap than adults alone. Hens and young together can be trapped in larger numbers, and more birds can be transported with less loss than when adults without young are trapped and transported. When hens with young are released, release sites can be selected with some assurance that the turkeys will remain there, whereas adult birds tend to seek their own range. If hens with broods are planted, adult birds stocked later will unite with the hens and broods and stay in the areas of release. The releasing of young birds may result in longer survival of breeding stock than if only adults are released, since adult mortality due to old age and/or hunting pressure is a factor in some areas.